2012
DOI: 10.5402/2012/971328
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Causes of Neck Pain and Disability as Perceived by Those Who Experience the Condition: A Mixed-Methods Study

Abstract: Designing effective treatment protocols for neck-related disability has proven difficult. Disability has been examined from structural, emotional, and cognitive perspectives, with evidence supporting a multidimensional nature. The patient's perspective of their condition has found increasing value for patient-centred, evidence-informed care. This cross-sectional study utilized descriptive thematic analysis to examine perceptions of causation in 118 people with neck pain. The Brief Illness Perceptions Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…They had received conflicting information (e.g., Q35) or information that did not fit their own experiences, which did not help to gain control over their situation. In addition, other studies also found that people associated multiple biopsychosocial factors with the onset or persistence of their neck pain [ 37 , 70 ]. In people with WAD, the influence of compensation and funding systems on obtaining optimal care to improve their condition was explicitly mentioned [ 27 ], while in the current study only one participant (out of eight people with traumatic neck pain and twelve people with non-traumatic neck pain) raised this as a concern.…”
Section: Discussionmentioning
confidence: 99%
“…They had received conflicting information (e.g., Q35) or information that did not fit their own experiences, which did not help to gain control over their situation. In addition, other studies also found that people associated multiple biopsychosocial factors with the onset or persistence of their neck pain [ 37 , 70 ]. In people with WAD, the influence of compensation and funding systems on obtaining optimal care to improve their condition was explicitly mentioned [ 27 ], while in the current study only one participant (out of eight people with traumatic neck pain and twelve people with non-traumatic neck pain) raised this as a concern.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence and chronicity of neck pain are further estimated to be 14% to 37%, respectively [ 3 ]. In most cases of neck pain, except for cases of diagnosed myelopathy and fracture, the pathomechanism of neck pain, similar to that of low back pain, is not fully understood [ 3 - 5 ]. Nevertheless, a variety of sensorimotor impairments have been observed in patients with neck pain, such as increased postural instability [ 6 ] and decreased cervical joint position sense (CJPS) acuity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%